Infant Feeding Guidelines for the Asia Pacific Region - Colin Binns; Mi, Kyung Lee; Masaharu Kagaa; Wah, Yun Low; Jane Scott; Andy Lee; Alfred Zerfas; Bruce Maycock; Liqian Qiu; Aza Yusuff; Raheema Abdul Raheem; Syarhul Hamid; et al. (2018)
Good nutrition for infants, during the first 1000 days from conception, is one of the most important determinants of a healthy long life. Breastfeeding is the most important component of infant nutrition and reduces morbidity and mortality. With the changes to the climate currently occurring, issues of nutrition and food supply are only going to increase in importance. The Sustainable Development Goals of the United Nations, place nutrition at the forefront of world development and a sustainable planet. The vision of Asia-Pacific Academic Consortium for Public Health (APACPH) is to “achieve the highest possible level of health of all the people of the nations of the Asia-Pacific region.” Much of the burden of disease, early deaths, and disability in the Asia Pacific region could be reduced with public health efforts to address the major risk factors, including nutrition-related causes and smoking. The United Nations Decade of Action on Nutrition 2016-2025 has recently been launched with the aim of reducing the global burden of inappropriate nutrition. The goals include increasing rates of exclusive breastfeeding to 6 months, reducing wasting and stunting, and reducing the rates of low birthweight. This is the position endorsed in these guidelines along with the principles of the Baby Friendly Hospital Initiative. These guidelines expand the information on infants that was included in the 2016 APACPH Dietary Guidelines. APACPH covers many different environments, geographical areas, cultures, and socioeconomic groups. These guidelines are generally applicable to all infants in our region, specific local advice may sometimes be needed.